2013
DOI: 10.1111/bjir.12024
|View full text |Cite
|
Sign up to set email alerts
|

Fixed‐Term Contracts: Short‐Term Blessings or Long‐Term Scars? Empirical Findings from theNetherlands 1980–2000

Abstract: Using a comprehensive longitudinal dataset of prime-age Dutch workers over the period 1980-2000, we examine how a previously held job with a fixed-term contract influences both the likelihood and the duration of a future spell of unemployment. Analyses show that Dutch workers with fixed-term contracts experience higher risks of future unemployment and have no shorter spells of unemployment compared to workers with regular contracts. Results also reveal that swifter employment re-entries among men with fixed-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…For men, these type of contracts work as a stepping-stone toward establishment on the labor market to a greater degree than for women. Mooi-Reci and Dekker (2015), in a longitudinal study, compared the risk of becoming unemployed between temporary and permanent employees in the Netherlands. They show that those who have previously been temporary employed have recurring periods of unemployment to a greater extent.…”
Section: Temporary Employment As a Stepping-stone Or A Blind Alley Fomentioning
confidence: 99%
“…For men, these type of contracts work as a stepping-stone toward establishment on the labor market to a greater degree than for women. Mooi-Reci and Dekker (2015), in a longitudinal study, compared the risk of becoming unemployed between temporary and permanent employees in the Netherlands. They show that those who have previously been temporary employed have recurring periods of unemployment to a greater extent.…”
Section: Temporary Employment As a Stepping-stone Or A Blind Alley Fomentioning
confidence: 99%
“…This introduces a twofold problem. First, as temporary employment may have a scarring effect, the career path of a worker is likely to influence a worker's probability to make the transition to a good labour market outcome as well as the duration until that transition takes place (Hopp et al, 2016;Mooi-Reci and Dekker, 2015;Pavlopoulos, 2013;Scherer, 2004). Second, a transition to permanent employment does not have to be a final outcome in the worker's career.…”
Section: Temporary Employment As a Stepping Stone Or A Trapmentioning
confidence: 99%
“…These surveys have revealed that the labor market is divided, between the workers with permanent, steady jobs (the so-called insiders) and those with a fixed-term employment contract (the outsiders). According to this insider/outsider pattern, the former have stable, well-paid employment and a high level of social protection and security, while the fixed-term workers hold a significant part of secondary economy, which provides unstable, unprotected jobs with low social rights and benefits; moreover, they can be easily dismissed in the event of economic crises (Mooi-Reci & Dekker, 2015). It has been found that these circumstances defining the "outsiders'" sphere entail higher risks of unemployment in the future for these workers.…”
Section: Disadvantages From the Employees' Standpointmentioning
confidence: 99%
“…It has been found that these circumstances defining the "outsiders'" sphere entail higher risks of unemployment in the future for these workers. Indeed, on the one hand the jobs taken by fixed-term workers are less skilled and easier to find, thus generating shorter unemployment periods; but on the other hand, these jobs are also more easily lost and consequently increase the risk of unemployment for the future (Mooi-Reci & Dekker, 2015). This is why the fixed-term employment contracts are associated with great potential precarity, expressed as follows: a) Regarding the job instability and the protection granted to the employees on a fixed-term employment contract.…”
Section: Disadvantages From the Employees' Standpointmentioning
confidence: 99%
See 1 more Smart Citation